Paleomagnetism and petrogenesis of Paleoproterozoic units from the Uatumã event in the northern Amazonian Craton - Antonio, Paul Yves Jean (2017)
An anorogenic magmatism covered a large part (1.500.000 km2) of the Amazonian craton at ca. 1880 Ma and defined a Silicic Large Igneous Province (SLIP) called the Uatumã event. The aim of this work is to study the paleomagnetism and petrology of these rocks to define the space-time framework of the Uatumã event and to try to elucidate the Amazonian craton evolution during the Columbia supercontinent amalgamation. Two regions were selected in the southwestern Amazonian craton (Pará) for sampling: (1) The Tucumã area where 16 felsic dikes, 7 mafic dikes, a gabbroic dike and 3 sites of the Archean basement were collected, and (2) the São Felix do Xingu area where, 7 sites of rhyolitic lava flows, 2 sites of ignimbrites, a felsic dike and a volcanic breccia belonging to the Santa Rosa Formation were sampled, and also 6 sites of the Sobreiro Formation (volcanoclastic rocks, andesitic) and one felsic dike of the Velho Guilherme Suite were collected. Petrology of the felsic dikes of Tucumã (1880.9 ± 6.7 Ma U-Pb zrn) showed that they represent the dike swarm associated with the Santa Rosa volcanic Formation. The remanent magnetization of the felsic dikes is carried by PSD magnetite and hematite. This hematite is syn- to post magmatic derived from hydrothermal fluids. Magnetic mineralogy can be used as a proxy to quantify the hydrothermal alteration. AF, thermal, LTD + AF and LTD + thermal demagnetizations show a northwest direction with a positive inclination (component A), whose site mean directions gives a paleomagnetic pole located at 52.9°S, 76.4°E, A95= 10.4 °, K= 13.52). However, this component seems to represent a remagnetization, probabily occurred at Neoproterozoic times. Another magnetic component (named component B) was also isolated for these rocks, and it was associated to a Mesozoic regional remagnetization related to the Central Atlantic Magmatic Province (CAMP). Yet, a third southwestern direction with low positive inclination (component C) was also isolated for some sites. This component was interpreted to be related with the ca. 1760 Ma Velho Guilherme magmatic intrusion. The best paleomagnetic results were obtained in the São Felix do Xingu area. Two new primary paleomagnetic poles have been determined: (i) SF1 pole (319.7°E, 24.7°S, N= 10; A95= 16.9 °) was obtained for andesites and rhyolites dated to 1877.4 ± 4.3 Ma (U-Pb zrn, LA-ICPMS), and its primary origin is confirmed by an inverse baked contact test (> 1853 Ma). Petrography shows that the magnetic mineralogy of this component is hematite formed by hydrothermal fluids syn- to post magmatic. (Ii) SF2 pole (220.1°E, 31.1°N, N= 15 ° A95= 9.7 °) was determined by the remanent magnetization of the felsic dike of the Velho Guilherme Suite but also as secondary magnetizations in samples of the Santa Rosa and Sobreiro Formations. An age of 1853.7 ± 6.2 Ma (U-Pb zrn, LA-ICPMS) is calculated for the felsic dike carrying SF2, whose primary origin is confirmed by a positive baked contact test. The SF1 and SF2 poles have a significant difference in angular distance, for a time interval of only ~25 Ma. Similar coeval paleomagnetic discrepancies were observed for other cratons (India, Superior (Laurentia), Slave (Laurentia), Kalahari, Baltica and Siberia), which can be explained by a True Polar Wander (TPW) event at ca. 1880 1860 Ma. This period is marked by a high mantle activity, which results in the amalgamation of the Columbia supercontinent, formed at ca. 1850 1800 Ma. Amalgamation of supercontinent may cause the formation of superplume and thermal insulation which can disturb mass distribution in mantle and alter the inertial gravity tensor of the Earth. A True Polar Wander (TPW) event may thus have taken place, which will move the cratons and the superplumes towards the equator. These conditions may be related to a reorganization of the whole mantle following a global magmatic quiescence between 2400 and 2200 Ma.